2011
DOI: 10.1002/jsfa.4456
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory and antioxidant potential of Lactobacillus exopolysaccharides

Abstract: 101EP and 102EP stimulate cell proliferation and may be useful as a mild immune modulator of macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(129 citation statements)
references
References 44 publications
4
118
0
7
Order By: Relevance
“…The particular chemical nature of the EPS could be the reason for its relatively low level of antioxidant property. Liu et al (2011) showed Lactobacillus EPS to have potent antioxidant activity. Chemical modification of the polysaccharide, such as alkylation, acylation, reduction, oxidation, sulphonation, etc., could improve the property.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The particular chemical nature of the EPS could be the reason for its relatively low level of antioxidant property. Liu et al (2011) showed Lactobacillus EPS to have potent antioxidant activity. Chemical modification of the polysaccharide, such as alkylation, acylation, reduction, oxidation, sulphonation, etc., could improve the property.…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al (2007) reported that macrophage activation by lactic acid bacteria EPS resulted in the release of TNF-α. The experiment by Liu et al (2011) proved that the EPS isolated from lactic acid bacteria can promote macrophage growth and induce production of pro-inflammatory responses in murine macrophage cell lines. The understanding of this complex process requires further in vitro and in vivo experiments.…”
Section: Antitumour Activity Of L Plantarum Eps Morphological Apoptomentioning
confidence: 99%
“…19 Once we extracted and purified EPS, we need to evaluate its functional and physiological properties by which we can conclude where and in which way it can be used commercially. Here in this research, we analyzed the antioxidant potential of this partially purified EPS in order to characterize its use either as food supplementing agent or in direct drug delivery system.…”
Section: Antioxidant Potentialmentioning
confidence: 99%
“…20 Recently huge attention has been focused to evaluate the biological and therapeutic potential of LAB derived EPSs to serve as natural antioxidantsas well as functional food supplements. 19,20 Polak-Berecka et al 11 reported antioxidant effects of EPSs and assumed that the structure-function and composition relationship in EPSs biopolymers play a crucial role for their specific biological actions. Although several studies have shown the antioxidant potential of microbial polysaccharides, 21,22 very limited information is available concerning the mechanisms of the antioxidant action of polysaccharides at molecular level.…”
Section: Antioxidant Potentialmentioning
confidence: 99%
“…Враховуючи дані літератури щодо антиокси-дантних властивостей пробіотиків [8,16], ми пе-ревірили гіпотезу про зменшення інтенсивності процесів ліпопероксидації в шлунку щурів при 14-добовому застосуванні пробіотиків.…”
Section: результати та їх обговоренняunclassified